2019
DOI: 10.1002/jsfa.9646
|View full text |Cite
|
Sign up to set email alerts
|

Saponin‐enriched extracts from body wall and Cuvierian tubule of Holothuria leucospilota reduce fat accumulation and suppress lipogenesis in Caenorhabditis elegans

Abstract: BACKGROUND Saponins have been shown to possess many pharmacological properties, including altered fat metabolism. The black sea cucumber, Holothuria leucospilota, is a marine animal that contains a specialized organ called a Cuvierian tubule that produces and secrete the bioactive saponins into the tubules and body wall. Therefore, the aims of this study are to investigate the anti‐obesity effect of saponins extracted from body wall and Cuvierian tubules of H. leucospilota. RESULTS The butanol extracts of H. l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Saponin-enriched extracts from Holothuria leucospilota significantly reduced the fat deposition and triglyceride levels in a high glucose fed Caenorhabditis elegans model by downregulating the messenger RNA expressions of genes involved in fat storage and metabolism, including sbp-1, cebp, and daf-16 and upregulating the expression of nhr-49 gene (Chumphoochai et al, 2019).…”
Section: Fucoidanmentioning
confidence: 95%
“…Saponin-enriched extracts from Holothuria leucospilota significantly reduced the fat deposition and triglyceride levels in a high glucose fed Caenorhabditis elegans model by downregulating the messenger RNA expressions of genes involved in fat storage and metabolism, including sbp-1, cebp, and daf-16 and upregulating the expression of nhr-49 gene (Chumphoochai et al, 2019).…”
Section: Fucoidanmentioning
confidence: 95%
“…We recently reported that H. leucospilota extracts exhibit an anti‐Parkinson effect in a C. elegans model of PD (Malaiwong et al, ). Another study from our laboratory also demonstrated that supplementation of H. leucospiota extracts can reduce fat deposition and triglyceride levels of a C. elegans model of obesity (Chumphoochai, Chalorak, Suphamungmee, Sobhon, & Meemon, ). However, little is known about whether H. leucospiota saponin is able to promote lifespan extension and stress resistance in any organisms and the mechanisms underlying an anti‐aging activity of H. leucospiota saponin has not been elucidated.…”
Section: Introductionmentioning
confidence: 68%
“…Although the type of lipids in C. elegans NL5901 was not investigated in this study, it is possible that H. leucospilota -derived palmitic acid might reduce the augmentation of toxic unsaturated fatty acids which then reduced the aggregation propensity of α-synuclein in NL5901 worms. Previous study demonstrated that the body wall extract of H. leucospilota reduced fat accumulation by downregulating lipogenesis in the C. elegans model of obesity [ 59 ]. However, the mechanistic aspects of this event need to be studied in more detail.…”
Section: Discussionmentioning
confidence: 99%